2010
DOI: 10.1086/657119
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load Predicts New World Health Organization Stage 3 and 4 Events in HIV‐Infected Children Receiving Highly Active Antiretroviral Therapy, Independent of CD4 T Lymphocyte Value

Abstract: Background Many resource-limited countries rely on clinical and immunologic monitoring without routine virologic monitoring of HIV-infected children receiving highly active antiretroviral therapy (HAART). We assessed whether HIV viral load (VL) had independent predictive value in the presence of immunologic and clinical data for the occurrence of new World Health Organization (WHO) stage 3 or 4 events (WHO events) among HIV-infected children receiving HAART in Latin America. Methods The NICHD International S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…The adult studies were from Africa [18][19][20][21][22][23][24][25][26][27][28][29], Asia [30,31], and South America [23], and the pediatric studies were from Africa [32][33][34] and Asia [35]. We excluded 16 studies because performance of the WHO criteria was not calculable from data presented [8,[36][37][38][39][40][41], authors evaluated different predictor variables than the WHO criteria [42][43][44][45][46], authors used different outcomes such as mortality and disease progression [47][48][49], or authors did not define virologic failure [50].…”
Section: Resultsmentioning
confidence: 99%
“…The adult studies were from Africa [18][19][20][21][22][23][24][25][26][27][28][29], Asia [30,31], and South America [23], and the pediatric studies were from Africa [32][33][34] and Asia [35]. We excluded 16 studies because performance of the WHO criteria was not calculable from data presented [8,[36][37][38][39][40][41], authors evaluated different predictor variables than the WHO criteria [42][43][44][45][46], authors used different outcomes such as mortality and disease progression [47][48][49], or authors did not define virologic failure [50].…”
Section: Resultsmentioning
confidence: 99%
“…La aparición de las infecciones oportunistas generalmente es consecuencia de la inmunosupresión provocada por la infección por VIH [29], pero infecciones oportunistas como tuberculosis pueden provocar aumento de la replicación del VIH [30]. En nuestro estudio se encontró que el porcentaje de pacientes con tuberculosis durante la TARGA fue el doble en el grupo FV, pero esto no obtuvo asociación en el análisis multivariado.…”
Section: Discussionunclassified
“…It is possible that disease severity positively impacts treatment adherence in paediatric patients. In contrast, a South American study demonstrated that experiencing a WHO stage 3 and 4 event during the course of treatment was positively associated with viral load > 5000 copies / ml (32). …”
Section: Discussionmentioning
confidence: 99%